Challenges in Implementing the Triple Elimination of Mother-to-Child Transmission: A Study from Coastal Region of Ambon, Indonesia - Liengga, Haris; Manuputty, Amanda Gracia; Resnawaldi, Arlen (Faculty of Medicine, Universitas Airlangga, 2025)
Background: HIV, syphilis, and hepatitis B can be transmitted during pregnancy, which can cause morbidity and mortality. Efforts to eliminate the transmission of IV, syphilis, and hepatitis B are contained in the Minister of Health Regulation through Antenatal Care services in community health centers by screening and case management of positive pregnant women. The coverage of triple elimination in Eastern Indonesia has not been implemented, especially in Ambon City, while the goal in 2022 is that 100% of pregnant women will be screened and managed to prevent perinatal transmission. Purpose: This study aimed to evaluate the implementation of triple elimination screening including coverage, completeness, and infection rates in Ambon City. Methods: This study is a descriptive retrospective analysis based on medical records from four Community Health Centers during the year 2022. Result: Among 1,666 pregnant women, only one of the four centers (25%) met the national screening coverage target. None achieved 100% test completeness. Syphilis showed the highest infection rate (up to 12.2%), while hepatitis B rates were below the national threshold (≤7.1%) in all centers. Conclusion: Ambon City's triple elimination screening implementation has not met national criteria. Enhancing program efficacy requires expanding access to screening services and bolstering health education.